Genetic characterization of third- or fourth-generation cephalosporin-resistant avian pathogenic Escherichia coli isolated from broilers - Kang, Hyo Jung; Lim, Suk-Kyung; Lee, Young Ju (Frontiers in Veterinary Science, 2022)
The third- or fourth-generation cephalosporins (3GC or 4 GC) are classified as “critically important antimicrobials for human medicine” by WHO, but resistance to these drugs is increasing rapidly in avian pathogenic E. coli (APEC). This study investigated the distribution and genetic characteristics of 3GC- or 4 GC-resistant APEC isolates from five major integrated broiler operations in Korea. The prevalence of 3GC- or 4GC-resistant APEC isolates in 1-week-old broilers was the highest in farms of operation C (53.3%); however, the highest prevalence of these isolates in 4-week-old broilers was the highest on the farms of operation A (60.0%), followed by operations E (50.0%) and C (35.7%). All 49 3GC- or 4GC-resistant APEC isolates had at least one β-lactamase-encoding gene. The most common β-lactamase-encoding genes was extended-spectrum β-lactamase gene, blaCTX-M-15, detected in 24 isolates (49.0%), followed by blaTEM-1 (32.7%). Sixteen isolates (32.7%) harbored class 1 integrons, and four isolates (8.2%) showed different gene cassette-arrangements. However, only 1 of 26 isolates harboring class 2 integrons carried a gene cassette. Furthermore, both CRISPR 1 and 2 arrays were detected in most isolates (36 isolates; 73.5%), followed by CRISPR 2 (18.4%) and CRISPR 1 (4.1%). Interestingly, CRISPR 2 was significantly more prevalent in multidrug resistant (MDR)-APEC isolates than in non-MDR APEC isolates, whereas CRISPR 3 and 4 were significantly more prevalent in non-MDR APEC isolates (each 11.1%; p < 0.05). None of the protospacers of CRISPR arrays were directly associated with antimicrobial resistance. Our findings indicate that the distribution and characteristics of 3GC or 4GC-resistant APEC isolates differed among the integrated broiler operations; moreover, improved management protocols are needed to control the horizontal transmission of 3GC or 4GC-resistant APEC isolates.